Factors Influencing Tooth Brushing Behaviour based on Health Belief Model among Bushehr Primary School 5th & 6th grade Students - Masoumeh Sadat Zare; Azita Noroozi; Rahim Tahmasebi (Tehran University of Medical Sciences, 2013)
Background & Aim: Oral health is one of the most important components of personal health. Understanding current status of oral health is necessary to provide future oral health interventions. The aim of this study was to determine factors influencing tooth brushing behavior based on the health belief model (HBM) among 5- and 6-grader students.   Methods & Materials : : In this cross-sectional study, 370 primary school students were selected using the stratified cluster sampling method. Data were collected using a questionnaires based on the HBM. The obtained data were analyzed in the SPSS-20.   Results: The results showed that 95.7% of the students brushed their teeth once or more daily. Mean and standard deviation of the brushing frequency in one week was 8.66±3.54. There was a significant correlation between the perceived barriers (P=0.00, r=-0.14) and self-efficacy (P=0.04, r=0.10) with the brushing behavior.   Conclusion : According to the results, educating students and decreasing different barriers seems to be necessary to improve brushing behavior.